Randomised clinical trial: efficacy and safety of vonoprazan vs. lansoprazole in patients with gastric or duodenal ulcers – results from two phase 3, non‐inferiority randomised controlled trials. Issue 2 (27th November 2016) - Miwa, H.; Uedo, N.; Watari, J.; Mori, Y.; Sakurai, Y.; Takanami, Y.; Nishimura, A.; Tatsumi, T.; Sakaki, N.
Summary: Background: Vonoprazan is a new potassium‐competitive acid blocker for treatment of acid‐related diseases. Aim: To conduct two randomised‐controlled trials, to evaluate the non‐inferiority of vonoprazan vs. lansoprazole, a proton pump inhibitor, for treatment of gastric ulcer (GU) or duodenal ulcer (DU). Methods: Patients aged ≥20 years with ≥1 endoscopically‐confirmed GU or DU (≥5 mm white coating) were randomised 1:1 using double‐dummy blinding to receive lansoprazole (30 mg) or vonoprazan (20 mg) for 8 (GU study) or 6 (DU study) weeks. The primary endpoint was the proportion of patients with endoscopically confirmed healed GU or DU. Results: For GU, 93.5% (216/231) of vonoprazan‐treated patients and 93.8% (211/225) of lansoprazole‐treated patients achieved healed GU; non‐inferiority of vonoprazan to lansoprazole was confirmed [difference = −0.3% (95% CI −4.750, 4.208); P = 0.0011]. For DU, 95.5% (170/178) of vonoprazan‐treated patients and 98.3% (177/180) of lansoprazole‐treated patients achieved healed DU; non‐inferiority to lansoprazole was not confirmed [difference = −2.8% (95% CI −6.400, 0.745); P = 0.0654]. The incidences of treatment‐emergent adverse events were slightly lower for GU and slightly higher for DU with vonoprazan than with lansoprazole. There was one death (subarachnoid haemorrhage) in the vonoprazan group (DU). The possibility of a relationship between this unexpected patient death and the study drug could not be ruled out. In both studies, increases in serum gastrin levels were greater in vonoprazan‐treated vs. lansoprazole‐treated patients; levels returned to baseline after treatment in both groups. Conclusions: Vonoprazan 20 mg has a similar tolerability profile to lansoprazole 30 mg and is non‐inferior with respect to GU healing and has similar efficacy for DU healing.